2021
DOI: 10.1002/app.51852
|View full text |Cite
|
Sign up to set email alerts
|

Squeeze flow in multilayer polymeric films: Effect of material characteristics and process conditions

Abstract: In this work, effects of sealing temperature, time, pressure, as well as sealant thickness and viscosity on squeeze out flow (SOF) in heat sealing were examined. A new image analysis approach is presented to quantify SOF in heat sealing. It was found that increasing temperature or pressure could improve SOF but only in thick 130 μm sealants and reducing the sealant thickness to 50 μm suppressed SOF. Reducing viscosity in 50 μm sealant films was also found to improve SOF only at high-sealing pressure and long s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…With thin seal layers, SOF is only increased at high seal pressure and long seal time if viscosity of seal material is reduced. A 10‐fold seal pressure increases SOF only with thick seal layers 58 …”
Section: Polyolefinsmentioning
confidence: 99%
“…With thin seal layers, SOF is only increased at high seal pressure and long seal time if viscosity of seal material is reduced. A 10‐fold seal pressure increases SOF only with thick seal layers 58 …”
Section: Polyolefinsmentioning
confidence: 99%
“…As for the dwell time, it is determined by the material requirements and the speed of the tool. It was also shown that in order to get a good seal, a minimum pressure is needed, however, a higher pressure is ineffective or even detrimental to the seal quality because it causes material squeeze flow 16,17 . T‐peel tests on single layered polymer films showed three types of failure, depending on the mechanical strength of the sealed zone: peeling, tearing and peeling + tearing 14 .…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that in order to get a good seal, a minimum pressure is needed, however, a higher pressure is ineffective or even detrimental to the seal quality because it causes material squeeze flow. 16,17 T-peel tests on single layered polymer films showed three types of failure, depending on the mechanical strength of the sealed zone: peeling, tearing and peeling + tearing. 14 It was also shown that for complex films, the same failure types were observed, but with 3 different ways for tearing failure: tearing of the entire film can happen at one side of the seal, or only a breaking of the sealant layer, while the third option is the tearing of the sealant layer with a delamination between the sealant and external layer of the films.…”
mentioning
confidence: 99%